1982
DOI: 10.1139/m82-165
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the total extractable lipids of Zymomonas mobilis var. mobilis

Abstract: The cells of Zymomonas mobilis var. mobilis contained 6.3% of the chloroform–methanol–water extractable lipids (dry weight basis) and 1.5% of bound lipids. The extractable lipids were 96.8% polar lipids and 3.2% neutral lipids. The neutral lipids contained squalene, and 21 pentacyclic triterpene hydrocarbons comprised 1.4% of the total lipids. The remaining neutral lipids consisted of relatively small quantities of components tentatively identified as free fatty acids, tri-, di-, and mono-glycerides, lipoamino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…1, 2) appear in agreement with a common view on the hydrophobic character of constituents in the polymorphic composition of cell envelopes from proteobacteria [11,22,26]. In fact, the range of carbohydrate concentration (7.82-47.12 g mg ¡1 dry mass) corresponds to an apparent content of LPS about 1.1-7.3% of the cell mass [11] being very comparable to that from various proteobacteria [22,26] including Z. mobilis ATCC 10988 [32].…”
Section: Discussionsupporting
confidence: 86%
“…1, 2) appear in agreement with a common view on the hydrophobic character of constituents in the polymorphic composition of cell envelopes from proteobacteria [11,22,26]. In fact, the range of carbohydrate concentration (7.82-47.12 g mg ¡1 dry mass) corresponds to an apparent content of LPS about 1.1-7.3% of the cell mass [11] being very comparable to that from various proteobacteria [22,26] including Z. mobilis ATCC 10988 [32].…”
Section: Discussionsupporting
confidence: 86%
“…This is somewhat surprising when one considers the differences in plasma membrane lipids between these two organisms. Z. mobilis contains large amounts of phosphatidylcholine and an extremely high proportion of vaccenic acid (8,20 …”
mentioning
confidence: 99%
“…A sample of dried lipid extract was treated with 72% perchloric acid at 150°C, and phosphate was determined colorimetrically after reaction with ammonium molybdate and ANSA reagent (4); diheptadecanoylphosphatidylcholine was used as the organic phosphorus standard. From the organic phosphorus content, the weight of phospholipids in the extract was estimated by using a mean phospholipid molecular mass of 730 g/mol, calculated on the basis of Z. mobilis phospholipid composition (7,30 on hopanoid content either. The organic phosphorus content, however, decreased at the highest growth rates, and as a result, the molar ratio of hopanoids to phospholipids increased from about 0.7 to between 0.9 and 1.0.…”
mentioning
confidence: 99%
“…For Z. mobilis it was shown that more than 70% of the fatty acids in the phospholipid fraction is cis-vaccenic acid, which appears to be suitable for an ethanol-tolerant microorganism (7,30). The most striking result, however, was the observation of considerable amounts of neutral hopanoids (6).…”
mentioning
confidence: 99%